2009
DOI: 10.1002/em.20458
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal aberrations in railroad transit workers: Effect of genetic polymorphisms

Abstract: Complex chemical mixtures are transported by train from Russia to Finland for further shipment. Here, we studied if exposure to genotoxic components among these substances could affect chromosomal aberrations (CAs) in peripheral lymphocytes of workers handling the tank cars. An initial survey among 48 railroad workers and 39 referents (male smokers and nonsmokers) showed an elevation of CAs. A campaign was started to reduce exposures through preventive measures. Five years later, 51 tank car workers and 40 age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…The first of these variants, C677T, has been shown to be associated with higher baseline homocysteine levels in the serum and is associated with increased risk of vascular disease and neural tube defects, and polymorphisms of A1298C may be risky factors of multiple tumors in several studies. In 2008, a study in Beijing area [19] [20,21], suggested that MTHFR gene polymorphisms were associated with individual chromosomal damage. Our results, consistent with these studies, raises the concerns that the effect of occupational exposure to BD may be significantly modulated by folate status which varies greatly amongst individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The first of these variants, C677T, has been shown to be associated with higher baseline homocysteine levels in the serum and is associated with increased risk of vascular disease and neural tube defects, and polymorphisms of A1298C may be risky factors of multiple tumors in several studies. In 2008, a study in Beijing area [19] [20,21], suggested that MTHFR gene polymorphisms were associated with individual chromosomal damage. Our results, consistent with these studies, raises the concerns that the effect of occupational exposure to BD may be significantly modulated by folate status which varies greatly amongst individuals.…”
Section: Discussionmentioning
confidence: 99%